2019
DOI: 10.2478/hacq-2019-0009
|View full text |Cite
|
Sign up to set email alerts
|

Iron age burial mounds as refugia for steppe specialist plants and invertebrates – case study from the Zsolca mounds (NE Hungary)

Abstract: Prehistoric mounds of the Great Hungarian Plain often function as refuges for relic loess steppe vegetation and their associated fauna. The Zsolca mounds are a typical example of kurgans acting as refuges, and even though they are surrounded by agricultural land, they harbour a species rich loess grassland with an area of 0.8 ha. With a detailed field survey of their geomorphology, soil, flora and fauna, we describe the most relevant attributes of the mounds regarding their maintenance as valuable grassland ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 20 publications
(31 reference statements)
0
8
0
8
Order By: Relevance
“…Due to their isolated state, the management of grassland fragments on kurgans has been ceased for decades or centuries. As they have been built using the topsoil of the neighboring areas, their soil is rich in nutrients and has a good physical structure (Tóth et al, 2019). Verges represented grassland fragments with a linear shape.…”
Section: Study Areamentioning
confidence: 99%
“…Due to their isolated state, the management of grassland fragments on kurgans has been ceased for decades or centuries. As they have been built using the topsoil of the neighboring areas, their soil is rich in nutrients and has a good physical structure (Tóth et al, 2019). Verges represented grassland fragments with a linear shape.…”
Section: Study Areamentioning
confidence: 99%
“…In their case study, Tóth et al (2019) show the importance of kurgans in nature conservation. They studied the geomorphology, soil parameters, vegetation and arthropod assemblages of a twin kurgan complex called the Zsolca mounds in Northeastern Hungary.…”
Section: Contributions Of the Special Issuementioning
confidence: 99%
“…Due to their steep slopes and social taboos associated with them, they have often remained intact from human disturbances such as ploughing, and thus may act as safe havens for grassland species across Eurasia 24 . Their unique hill shape with steep slopes results in the formation of different microhabitats (e.g., slopes with different aspects) characterised by different abiotic parameters such as soil nutrient content and soil moisture 26 , 27 . Previous studies showed that these abiotic patterns result in the formation of distinct microhabitats 17 , 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, despite their relatively small area, mounds are characterised by a diverse mosaic of microhabitats and a high plant diversity 17 , 25 . Despite the fauna is an integral part of dry grassland communities preserved by the mounds, most studies focused on their vegetation, and only a few researches dealt with their fauna (but see Marcolin et al 29 ; Deák et al 12 and Tóth et al 26 ).…”
Section: Introductionmentioning
confidence: 99%